2011
DOI: 10.2486/indhealth.ms1257
|View full text |Cite
|
Sign up to set email alerts
|

Relationship between Autonomic Nervous System Activity during Sleep and Fasting Glucose in Japanese Workers

Abstract: Although autonomic nervous system activity is reportedly related to diurnal glucose tolerance impairment, the relationship with glucose tolerance during sleep is unclear. Since work styles have recently diversified, it is important to assess the effect of sleep on workers' health. Elucidation of the relationship between autonomic nervous system activity during sleep and glucose tolerance in workers may facilitate preventive measures against diabetes using nonpharmacological means (e.g., sleep hygiene education… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
2
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 38 publications
1
2
0
Order By: Relevance
“…This suggestion also seems to be in line with previous studies that showed that parasympathetic activity was negatively correlated with decreased glucose during overnight fasting [22]. It should be mentioned here that in our study, glucose concentration after 8 days of water-only fasting was also decreased, which, according to the above suggestions, may indicate parasympathetic stimulation reducing SBP.…”
Section: Changes In the Cardiovascular System After Fasting And Exercisesupporting
confidence: 93%
“…This suggestion also seems to be in line with previous studies that showed that parasympathetic activity was negatively correlated with decreased glucose during overnight fasting [22]. It should be mentioned here that in our study, glucose concentration after 8 days of water-only fasting was also decreased, which, according to the above suggestions, may indicate parasympathetic stimulation reducing SBP.…”
Section: Changes In the Cardiovascular System After Fasting And Exercisesupporting
confidence: 93%
“…Loaded physical exercise was evaluated based on levels of serum enzyme proteins derived from muscles (creatine phosphokinase [CPK] and lactate dehydrogenase [LDH]). Using a wearable watch-type wrist bundled sensor with a finger sensor [23], the quality and quantity of sleep during an entire night were evaluated before and during the training.…”
Section: Introductionmentioning
confidence: 99%
“…The wearable physiological sensor was 55 × 57 × 14 mm in size, weighed 40 g, and operated on a rechargeable battery. Like in actigram analysis, the activity levels during sleep were analyzed using a three‐axis accelerometer, where values greater than 0.1 G were analyzed with Cole's algorithm (Cole, Kripke, Gruen, Mullaney, & Gillin, ; Inano, Mizumori, Kobayashi, Sumiya, & Yatani, ; Kamata et al., ).…”
Section: Participants and Methodsmentioning
confidence: 99%